Instilling Religious Moderation Values Through Islamic Religious Education in Urban Primary School Children - Ahmadi, Ahmadi; Amalia, Riadlatul; Musleh, Musleh; Fattah, Mohammad; Supriyadi, Supriyadi (Maharot : Journal of Islamic Education, 2024)
Respecting differences is one form of a good person. Implementation of one's manners. Manners are part of what education aims to achieve. In fact, manners itself is the meaning of education itself, which can be interpreted by instilling manners in humans.Educational institutions play an important role in making students, as members of society, civilized or noble. Educating learners must be done early in early childhood education. Islamic Religious Education and Ethics (PAIBP) is one of the educational materials taught in elementary schools.This research examines how the values of religious moderation are instilled through Islamic Religious Education and Ethics (PAIBP) in elementary school children in urban areas, with a focus on SDN Pajagalan I Sumenep which is located in an urban area and has pluralistic students, both in terms of religion and cultural background. This research uses a qualitative, case study approach. With data sources coming from teachers, students and guardians of non-Muslim students. Data collection was done by interview, observation and documentation. The data was analyzed using interactive model analysis. Checking the validity of the data is done by extending observation, triangulation and checking the results with the PAIBP teacher at school.The results revealed that inclusive and tolerant religious education plays a significant role in shaping attitudes of tolerance and harmony among students with various religious backgrounds. Religious moderation in this school is implemented through various methods and approaches, both in formal learning in the classroom and through extracurricular and religious activities.The cultivation of religious moderation values not only creates a harmonious school environment but also contributes to broader social stability. Moderate religious education has proven to be effective in preventing radicalism and extremism in urban communities, thereby shaping a young generation that is moderate and able to live harmoniously in a multicultural society. These findings confirm the importance of inclusive religious education as a strategic solution to the challenges of diversity and enhancing interfaith harmony.